A note on the asymptotic behaviour of axisymmetric stagnation-point flow and heat transfer of a viscous fluid past a permeable stretching/shrinking cylinder. (November 2022) - Lok, Y.Y.; Pop, I.; Merkin, J.H.
Abstract: The forced convection flow near a stagnation point on a stretching/shrinking cylinder derived originally by Wang [1] and later extended by Lok and Pop [2] is further considered through obtaining the asymptotic behaviour for the relevant dimensionless parameters, namely the Prandtl number σ, the wall velocity λ, the wall transpiration rate S and the Reynolds number R . Additional numerical results are also obtained to confirm our asymptotic predictions. Critical values are seen in the numerical results for negative values of λ with an asymptotic solution valid for large negative λ gives an asymptotic expression for these critical values. It is found that multiple solutions are possible for the limiting range of shrinking and suction parameters. Besides, the asymptotic behaviour is similar for the case of large suction and large Reynolds number. Also, the asymptotic analysis shows that for the solution to continue to large shrinking parameter, the suction parameter should be positive and large.